Application of the sequence ultra/nanofiltration for valorization and reduction of the environmental impact of ovine cheese whey - Macedo, A. (2014)
The by‐products of agro‐industries, due to its high content of nutritive substances, in particular proteins and carbohydrates, have been the subject of intense investigation with a view to their recovery/reuse, towards sustainability. One of these by‐products is ovine cheese whey, that is mainly produced in Southern European countries, as a result of the production of ovine cheeses of Protected Designation of Origin. In most cases, that whey is disposed off into public sewage, causing problems in conventional treatment plants, due to its high organic load. In some countries, e.g. Portugal, Spain and Italy, part of the ovine cheese whey is further processed to obtain whey cheeses, designated by different names, such as requeijão, requesón and ricotta. However, not all of these cheese whey can be transformed due to the high volumes generated. Membrane technology has emerged as a significant innovation for recovery and treatment, because it is more economical than other alternatives, require much less land area than competing technologies and may produce water suitable for multiple proposes. In this work, an example of using membrane processes in the recovery of ovine cheese whey is presented. The operations of ultrafiltration (UF) and nanofiltration (NF) of ovine cheese whey were investigated with the objective of producing added‐value products, such as protein concentrates by UF, lactose concentrates by NF and final permeates with a very low organic load. UF experiments were performed with skimmed cheese whey, both in total recirculation and concentration modes. The equipment used was a plate‐and‐frame unit (Lab Unit M20). Ultrafiltration was performed with organic membranes ETNA 10PP with a surface area of 0,072 m2 and a cut‐off of 10 kDa. Ultrafiltration allowed a clear separation between the protein fraction and a fraction rich in lactose and minerals. About 40% of organic matter, expressed as COD was retained. Nanofiltration of UF permeates was done with membranes NFT50 with a membrane surface area of 0,072 m2..This operation allowed a high retention of lactose (98.8%) and the production of a permeate with a very low organic load. The retention of organic matter, in terms of COD was about 93%. The sequence of operations UF/NF allowed to produce two added‐value products, reducing at the same time the organic pollution of the final stream. Nevertheless, the quality of the final water should be assessed, according with the intended use.